Emerging Adult Relationship Transitions as Opportune Times for Tailored Interventions. (August 2017) - Vennum, Amber; Monk, J. Kale; Pasley, B. Kay; Fincham, F. D.
The goal of this research was to identify predictors of college students' relationship dissolution and how a relationship education (RE) curriculum integrated into a college course ( Relationship U [ RU ]) influenced students' breakup (BU) and relationship formation decisions. Study 1 ( n = 854) showed the strongest predictors of BU by the end of the semester were low relationship efficacy, dedication, satisfaction, and relationship length and greater emotional safety, distance, and extradyadic behavior. Study 2 ( n = 7, 957) examined the perceived influence of RU on students' decisions to end and begin relationships through thematic analysis of open-ended questions asking participants to identify what (if any) aspect of the curriculum influenced their decisions. Participant responses highlighted specific RE components differentially salient to their decisions to end and begin romantic relationships. Implications for creating tailored and adaptive RE curricula with emerging adults are discussed.